The uncomfortable chair of the colonial past and racist present an effective approach to white discomfort in the Netherlands - Kolman, Kiki (Department of Computer Science, 2023)
Activists, artists, academics, and other experts have pointed out the problem of (manifestations of) white discomfort in the Netherlands: white Dutch people experience strong unease when topics like racism or the colonial past are addressed, resulting in defensiveness and avoidance of important conversations – hence, obstructing the anti-racism struggle. In order to tackle this problem, it is important to understand where white discomfort is rooted and how it manifests. Gloria Wekker's work shows the importance of ‘white innocence' in understanding Dutch whiteness – the false conception of (progressive) Dutch white people that the Netherlands and they themselves are innocent with regard to racism. This myth of innocence is constructed on a collective national level. International literature on white discomfort, however, is often (but not always) focused on the individual's psychology. Therefore, this interdisciplinary thesis explores an additional conception of white discomfort, grounded in the Dutch reality, that acknowledges the historical and collective context of whiteness. This is done by combining critical whiteness studies with Affect Theory, specifically Sara Ahmed's work on whiteness and discomfort. The result is an understanding of white discomfort as the friction between the historically shaped self-perceived innocent body, and the historically shaped and continuously changing space this body is in. The conceptualisation is then further developed in a dance between theory and practice by analysing the results of focus groups with (self-identified) progressive white Dutch people. The research points to white discomfort as an interplay of 1) the identification of the individual with the collective of white Dutch people, or simply with the Netherlands as a country; 2) the collision with the innocent self-image when this collective collides with the innocent self-image; 3) the white person's desire to either be good or be perceived as good (most likely, a combination of both); And 4) the restricted space to speak in conversations on racism. The approach of white discomfort as affect, then, offers the opportunity to connect the white individual to the collective history of the Netherlands, while still acknowledging individual responsibility. And it helps uncover how the avoidance of white discomfort by individuals maintain problematic forms of whiteness.